THE ROLE OF ROBOTICS IN THE AGE OF DIGITAL TECHNOLOGIES - Umaraliyev, Jamshidbek To‘xtasin o‘g‘li; Turdaliyev , Kamronbek Ilhomjon o‘g‘li; Isoqjonova , Sarvinoz Ilhomjon qizi (Educational Research in Universal Sciences, 2023)
This essay explores the significant role of robotics in the digital age, focusing on its contributions, challenges, and future prospects. The author begins by highlighting automation as a key aspect of robotics, emphasizing its ability to enhance productivity and efficiency by relieving humans from repetitive and labor-intensive tasks. The essay further examines the advancements robotics has brought to the healthcare sector, such as surgical robots and robotic exoskeletons, which have revolutionized medical procedures and improved patient outcomes. The exploration of remote and hazardous environments through robotics is also discussed, showcasing how unmanned vehicles have enabled data collection and task execution in areas inaccessible to humans. The essay acknowledges the social and ethical considerations that arise from increased automation, emphasizing the importance of supporting workers in transitioning to the digital age and addressing concerns related to privacy and human-machine interactions. The future prospects of robotics are explored, including advancements in artificial intelligence, machine learning, and human-robot collaboration. The essay concludes by emphasizing the need for responsible integration of robotics, considering social, ethical, and regulatory factors to ensure a balanced and beneficial impact on society. Overall, this essay provides a comprehensive overview of the multifaceted role of robotics in the digital age, highlighting its transformative potential and the challenges that must be addressed for its responsible implementation.